From LED to solid state lighting : principles, materials, packaging, characterization, and applications /: principles, materials, packaging, characterization, and applications. (2021) - Lee, Shi-Wei Ricky; Lo, Jeffery C. C; Tao, Mian; Ye, Huaiyu
No abstract available